Flipped learning for teaching biostatistics to peruvian dental students - Teresa Evaristo-Chiyong; Manuel Mattos-Vela (Journal of Oral Research, 2019)
Objective: To evaluate the effect of the application of a flipped learning model for teaching biostatistics to dental students in a Peruvian public university. Methodology: A quasi-experimental, crossover, longitudinal and prospective design was used. A non-probability sampling technique was employed. The sample consisted of 63 students that enrolled in the Biostatistics course at the School of Dentistry at Universidad Nacional Mayor de San Marcos. Students were divided into two groups according to their designated training schedule. The contents of two units were assessed. For the first unit (descriptive statistics), the first group was taught using the flipped learning model and the second group with the master class model. For the second unit (inferential statistics), groups were crossed over. At both periods of the study, cognitive, procedural and attitudinal skills were assessed through previously validated questionnaires. Mann-Whitney U test, Cohen is d and multiple linear regression analysis were performed. Results: the mean total score for the second unit was higher (p<0.001) in the flipped learning group (32.58) compared to the master class guided training group (27.94), presenting a Cohen’s d=0.97. Procedural (9.23 versus 7.80) and attitudinal (15.63 versus 12.90) skills were on average higher in the flipped learning group. Regression analysis resulted in R2=0.245, p=0.003. Conclusion: the flipped learning method achieved a higher content learning in the second unit, compared to the master class model.